PID controller for idle speed control - Tuan Kamaruddin, Tengku Nordayana Akma; Mat Darus, Intan Zaurah, (IEEE, 2013)
The performance comparison of PID controllers for idle speed control internal combustion engine (ICE) is presented in this paper. There are three methods of PID tuning applied: heuristic tuning, self-tuning by pole placement, and also iterative learning algorithm (ILA). Prior to that, data collection is gained from four cylinder sparkignition engine modeling and used as the input-output data in the system identification part. The obtained transfer function from RLS technique is used in the development of the control system for the idle speed control by PID controllers. The main objective of the idle speed control is to maintain the idling speed at 650rpm and to reject as quickly as possible the extra load exerted on the engine system during idling mode. Comparing the three methods, it shows that PID tuning by ILA produced better results than heuristic tuning and pole placement.